Minutiae Matching Algorithm For Partial Fingerprints (International Journal of Engineering and Computer Science, 2017)
A fingerprint is an impression of ridges left behind on the surface of an object when they are touched or handled. Each person has own fingerprints with the permanent uniqueness. Because of this reason fingerprints are considered to be the excellent way of personal identification for criminal investigation purposes. The fingerprints encountered at crime scenes called partial fingerprints plays an important role in identifying criminals. Partial fingerprint matching also plays an important role in identifying suspects and criminals. In this paper we have proposed a minutiae matching algorithm to improve the performance of matching and reduces the time for matching. The proposed work reconstructs the orientation field of partials and iteratively matches the minutiae of partials and list of rolled and plain candidates that are initially matched. The main purpose of minutiae matching algorithm is to improve the matching rate and reduce the computational time in matching minutiae and also reduces the fault ratio.